2017
DOI: 10.1016/j.oraloncology.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of oral cavity cancer patients treated with surgery followed by postoperative intensity modulated radiation therapy

Abstract: Objectives Although treatment paradigms have not changed significantly, radiotherapy, surgery, and imaging techniques have improved, leading us to investigate oncologic and survival outcomes for oral cavity squamous cell cancer (OCSCC) patients treated with surgery followed by postoperative IMRT. Material and Methods Records of patients with pathological diagnosis of OCSCC treated between 2000–2012 were retrospectively reviewed. Patients’ demographic, disease, and treatment criteria were extracted. Kaplan-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
(22 reference statements)
2
16
0
1
Order By: Relevance
“…reported a significantly lower recurrence-free survival and a higher incidence of local recurrence in heavier smokers (Fang, Shi, Liu, & Sun, 2014), but another study reported significantly improved local control rates in patients who smoked more than 20 PY compared to non-smokers (Quinlan-Davidson et al, 2017). Besides, in a prognostic factor analysis of 85 patients with stage I-II oral tongue cancer treated primarily by surgery, 5-year relapse-free survival showed no significant difference by smoking status (75% with smoking versus.…”
Section: Discussionmentioning
confidence: 95%
“…reported a significantly lower recurrence-free survival and a higher incidence of local recurrence in heavier smokers (Fang, Shi, Liu, & Sun, 2014), but another study reported significantly improved local control rates in patients who smoked more than 20 PY compared to non-smokers (Quinlan-Davidson et al, 2017). Besides, in a prognostic factor analysis of 85 patients with stage I-II oral tongue cancer treated primarily by surgery, 5-year relapse-free survival showed no significant difference by smoking status (75% with smoking versus.…”
Section: Discussionmentioning
confidence: 95%
“…A study carried out in the Netherlands, from 1989 to 2011, demonstrated that patients diagnosed with oral and oropharyngeal SCC responded better to treatments, increasing the survival rate to 67 and 48%, respectively, in cases of oral cavity and oropharyngeal cancers [23]. Quinlan-Davidson et al studied 289 patients with OSCC who were treated with surgery followed by postoperative intensity modulated radiotherapy and observed a 5-year overall survival of 57% [24]. Some authors reported that survival rates were better in more developed countries than in developing ones [25].…”
Section: Discussionmentioning
confidence: 99%
“…Quinlan-Davidson et al studied 289 patients with OSCC who were treated with surgery followed by postoperative intensity modulated radiotherapy and observed a 5-year overall survival of 57% 24 .…”
Section: Discussionmentioning
confidence: 99%